A brief review on emerging trends in global polyphenol research. Issue 4 (13th February 2018) - Adebooye, Odunayo C.; Alashi, Adeola M.; Aluko, Rotimi E.
Abstract: This article is focused on the global trend in research with special emphasis on the economic importance of polyphenols. We examined some of the media used for the formulation of polyphenol‐enriched products. The levels of polyphenol extract production, international research funding, and number of published research work were determined from various databases and publicly available reports. The quantity of industrially extracted polyphenols was estimated to be 16, 380 tons in 2015 and this is anticipated to reach a total of 33, 880 tons by the end of 2024 with an estimated monetary value of USD 1.33 billion. Industrial utilization of polyphenol is dominated by the functional beverages sector (44%), followed by functional foods (33%) primarily due to high demands for polyphenol‐rich consumables. Within a 10‐year period, the number of polyphenol‐related publications doubled from 2006 (1, 574) to 2012 (3, 330) and almost tripled in 2015 (4, 213). Practical applications: Polyphenols remain one of the most researched bioactive food compounds because of their wide distribution in nature and also due to their versatility as agents that can improve human health and enhance the shelf‐life of foods. This report combines available scientific knowledge on the various factors that dictate polyphenol synthesis in plants, extraction methods, and utilization. The report also provides information on global polyphenol research and project funding history, which could serve as a critical reference for researchers all over the world.